Implementation of Image Distortion to Design Mockups in Web-Based Mug Sales Application - Kristy Tiffani (Sistemasi: Jurnal Sistem Informasi, 2023)
Varisty Mug Souvenir is a small business entity that provides services to make custom souvenir mugs according to customer requests. Souvenir mugs are the main product produced by Varisty Mug Souvenir. When the COVID-19 pandemic hit, Varisty Mug Souvenir's main shop was forced to close, this resulted in disruption of transactions between customers and owners and Varisty Mug Souvenir's sales decreased. aims to increase its sales and simplify the business transaction process by designing a web-based mug sales application with the feature of creating mug design mockups. The mug design mockup creation feature on the application will help customers visualize and make design decisions when placing an order. The development of a web-based mug sales web application will use the Hypertext Preprocessor (PHP) programming language and use the Laravel framework and MySQL database. The creation of the mug design mockup feature uses ImageMagick technology for the feature of generating mug design mockups that apply image distortion. The use of ImageMagick is done by running the command script on the command-line. In the application, customers can place an order for a custom mug by previewing the mug mockup of the desired design. In addition, the admin part of the application allows the admin to process and store data.